UX debt in an agile development process: evidence and characterization - Rodríguez, Andrés (2022)
The metaphor of technical debt (TD) has generated a conceptual framework on factors that weaken the quality of software and accumulate a repair cost. However, user-related aspects like user experience (UX) receive little consideration among TD types, for reasons like the substantial focus on code TD, some dynamics inherent to agile processes, and an apparent lack of cumulative cost over time. This article has two main goals: frst, to present evidence of the existence of UXDebt as a type of TD, with a cumulative cost for the development team as well as stakeholders; second, to propose a defnition and characterization of UXDebt that may serve as a frame for further research on methods and tools for continuous management within agile processes. For the frst goal, we have compiled evidence on the current state of UXDebt from three sources: a literature review, a survey among software engineering professionals in agile teams, and the analysis of UX issues in GitHub. All sources have evidenced some form of UXDebt; surveyed practitioners have recognized its poor management with a cost for the entire team that accumulates over time. Moreover, issue tracking systems allow to visualize and measure a technical form of UXDebt. For the second goal, we have defned a conceptual model that characterizes UXDebt in terms of both technical and non-technical aspects. On the technical side, we propose the notion of UX smells which allows us to discuss concrete management activities